A computerized cataloging management system for health science audiovisuals. - Metz, K S (1981)
This paper describes the implementation of the Stanford Public Information and Retrieval System (SPIRES) by the University of Michigan Medical School Learning Resources Center. SPIRES is a bibliographic data base management system which offers on-line search capabilities and retrieval of data in programmable formats. The Learning Resource Center utilizes SPIRES for the interactive retrieval of cataloging data, bibliographical compilations, and book catalog production.